2017
DOI: 10.1111/add.13888
|View full text |Cite
|
Sign up to set email alerts
|

Does coffee consumption impact on heaviness of smoking?

Abstract: Background and AimsCoffee consumption and cigarette smoking are strongly associated, but whether this association is causal remains unclear. We sought to: (1) determine whether coffee consumption influences cigarette smoking causally, (2) estimate the magnitude of any association and (3) explore potential mechanisms.DesignWe used Mendelian randomization (MR) analyses of observational data, using publicly available summarized data from the Tobacco and Genetics (TAG) consortium, individual‐level data from the UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
1
14
2
Order By: Relevance
“…In the other direction, a recent comprehensive three‐part study reported some evidence for a causal, negative effect of caffeine use on CPD with a two‐sample MR method on summary‐level data, but not with MR on individual‐level data or in‐vitro experiments . With a slightly different genetic instrument, we also found mainly negative effect sizes of caffeine use on CPD, but these were not significant.…”
Section: Discussioncontrasting
confidence: 55%
“…In the other direction, a recent comprehensive three‐part study reported some evidence for a causal, negative effect of caffeine use on CPD with a two‐sample MR method on summary‐level data, but not with MR on individual‐level data or in‐vitro experiments . With a slightly different genetic instrument, we also found mainly negative effect sizes of caffeine use on CPD, but these were not significant.…”
Section: Discussioncontrasting
confidence: 55%
“…When individual-level data are available, a common strategy is to restrict SNP-outcome analysis to coffee drinkers arguing that the SNPs are associated with coffee drinking (heaviness) and thus causal relationships should only be observed among coffee drinkers (a form of gene-environment interaction) [ 43 , 44 , 48 , 49 , 56 , 59 , 66 ]. SNP-outcome associations among non-drinkers (‘negative control sample’) would suggest a violation in at least one of the assumptions [ 59 , 66 ].…”
Section: Key Challenges To Mr Studies Of Coffee and Caffeinementioning
confidence: 99%
“…Potential mechanisms include shared genetic and/or shared environmental factors (i.e., common liability) or a causal influence of one on the other [ 71 ]. The co-occurrence of coffee/caffeine use with other substance use behaviors has been investigated in four MR studies [ 46 , 48 , 49 , 51 ]. Three of these studies employed bidirectional MR [ 46 , 49 , 51 ], in which IVs for each substance use were used to evaluate causal effects and their direction [ 23 , 72 ].…”
Section: Mr Studies Of Coffee Caffeine and Healthmentioning
confidence: 99%
See 2 more Smart Citations